Monitorowanie wypowiedzi a realizacja intencji w procesie mówienia - Bręński, Szymon (Człowiek i Społeczeństwo, 2020)
Speech production is complex and high organized process. It starts with some intention, which in following steps is transformed into articulated and audible form. Sometimes speech production fails and results in a speech error (or a slip of the tongue), which changes meaning of the utterance and disturbs the process of the realization of intention. However, speech monitoring helps to detect and repair the error with respect to the original intention of the speaker. Thus the speaking appears as a way of the realization of intention and the intention plays integrational function in relation to the process of speaking. According to Frydrychowicz (1999), the process of the realization of intention can be divided into several phases, distinguished by psychophysical features of speaking. He found that voice intensity is highest when the speaker is close to fully realizing the intention. The aim of the current study is to examine this voice intensity effect in relation to speech error repairs as speaking units which re-establish the process of the realization of intention. The question is, how these corrections of the course of speech are reflected in the voice intensity? The results obtained from errors and repairs induced in the dual task paradigm show that voice intensity rises when the speaker makes a self-repair by speaking a correct word.